PRENATAL DIAGNOSIS - Valeriu Popescu; Andrei Zamfirescu (Amaltea Medical Publishing House, 2009)
Another reproductive option that is now available is prenatal diagnosis. By utilizing increasingly sophisticated technology, many congenital malformations and genetic defects can now be diagnosed prior to twenty weeks of pregnancy. The authors present: 1. Couples at risk 2. Techniques used for prenatal diagnosis: X-rays; amniography; fetoscopy; echography; amniocentesis; chorionic willi sampling (CVS); 3. Conditions amenable to prenatal diagnosis (chromosome abnormalities, CNS closure defects, metabolic diseases, X-linked recessive diseases, hemoglobinopathies, miscelaneous); 4. Prerequisites for prenatal diagnosis; 5. Reaction of couple to prenatal diagnosis